2021
DOI: 10.14742/ajet.7207
|View full text |Cite
|
Sign up to set email alerts
|

The Continuous Pursuit of Smart Learning

Abstract: With an emphasis on learning flexibility, effectiveness, efficiency, engagement, adaptivity and reflectiveness, smart learning embraces a variety of concepts, including but not limited to personalised learning, adaptive learning, intelligent tutoring, open online learning, blended learning, and collaborative learning. As new concepts continue to evolve, the pursuit of smart learning is ongoing, mainly in areas pertaining to the design and implementation frameworks, pedagogical theories and practices, learners’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…They showed a relatively strong desire for interaction and cooperation among students and they were more likely to perceive the simplicity and usefulness of technology. They also tended to favour utilising technology to explore various ways to enhance their learning (Cheung & Wang, 2021). The findings echo the results of the study conducted by Y.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…They showed a relatively strong desire for interaction and cooperation among students and they were more likely to perceive the simplicity and usefulness of technology. They also tended to favour utilising technology to explore various ways to enhance their learning (Cheung & Wang, 2021). The findings echo the results of the study conducted by Y.…”
Section: Discussionsupporting
confidence: 69%
“…Third, it is necessary to reconstruct the evaluation criteria of smart classrooms and incorporate the improvement of students' information literacy as an important indicator. The ultimate goals of building smart classrooms are to guide students to become self-directed learners and help students acquire 21stcentury competencies, such as information literacy (Cheung & Wang, 2021). Consequently, relevant institutions and organisations should develop assessment standards for the effectiveness of smart learning environments, which not only include relevant content of technological solutions but also focus on the development of students' information literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that smart classrooms provide opportunities for students to use digital learning resources and tools in their self-regulated learning and collaborative inquiry learning activities ( Zhang et al, 2019 ). Obviously, instructors could obtain more support for trying the new pedagogies with mobile terminals in smart classrooms ( Zhan et al, 2021 ); and students demonstrated relatively stronger desire for interaction and tendency for utilizing the technology to enhance their learning in the smart classrooms ( Cheung and Wang, 2021 ). For example, Mimouni (2022) found that students were more engaged in learning by using clickers for interaction; and group interaction was also improved, with the pedagogy being changed from teacher-centered to student-centered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature [ 8 ] analyzes the feasibility of applying LBS to the group buying industry and discusses the existing problems and suggestions for improvement of the group buying website based on LBS. Literature [ 9 ] summarizes and analyzes the mobile e-commerce marketing model based on LBS based on relevant cases in the field of mobile e-commerce and predicts the development trend of mobile e-commerce based on LBS. Literature [ 10 ] proposed the prospect of mobile development of LBS business and the strategy of LBS application innovation through the SWOT analysis model and carried out a simple LBS system planning and design for the industrial application of LBS personal products with practical needs.…”
Section: Related Workmentioning
confidence: 99%